How Celebgram Credibility Influence Muslim Consumer’s Atitude Toward Purchase Decision? - Deasy Tantriana; Sudarmiatin; Agus Hermawan (International Journal Of Humanities Education and Social Sciences (IJHESS), 2022)
The purpose of this study is to investigate the impact of celebgram credibility and social media advertaising to purchase intention and the mediating of consumer muslim behavior at Nadira. The study conducted is quantitative  research  based  on  a  survey  approach. Purposive  sampling  and ordinary least  square regression were used as sampling techniques and data analysis. An online survey was conducted 119 muslim respondents with Nadiraa’s active Instagram followers. We analyzed the data using partial least squares structural equation modeling (PLS-SEM). The result show that Social Media Advertising and celebgram credibility  has a significant effect on Purchase Decision, while Influencer Marketing has no influence on Purchase Decision The results confirmed the significance of muslim consumer behavior in predicting purchase decision. In determining the number of samples, this study refers to Ferdinand theory, which is a theory for determining the sample by multiplying the number of indicators by the number of parameters estimated 5 to 10 times with a minimum of 5 times, and the size of sample ranges from 100 to 200 with a minimum of 100 sample. In this study there are 2 independent variables, namely social media advertising (X1) consists of 4 indicators and selebgram credibility  (X2) consists of 3 indicators, the dependent variable (Y) is purchase decision consists of 4 indicators, and moderating variables  (Z) muslim consumer behavior consisting of 5 indicators. the calculation results, the number of samples in this study were 119 respondents.